The effect of phase transformations on the recovery of pulsed electron beam irradiated Ti-6Al-4V titanium alloy during scratching; Journal of Alloys and Compounds; Vol. 795 - Sinyakova E. A. Elena Aleksandrovna; Panin A. V. Alexey Viktorovich; Perevalova O. B. Olga Borisovna; Shugurov A. R. Artur Rubinovich; Kalashnikov M. P. Mark Petrovich; Teresov A. D. Anton Dmitrievich (2019, 2019)
Title screen